Elementary bounds on the ruin capital in a diffusion model of risk - Vsevolod K. Malinovskii (Risks, 2014)
In a diffusion model of risk, we focus on the initial capital needed to make the probability of ruin within finite time equal to a prescribed value. It is defined as a solution of a nonlinear equation. The endeavor to write down and to investigate analytically this solution as a function of the premium rate seems not technically feasible. Instead, we obtain informative bounds for this capital in terms of elementary functions.
Keywords: 330; level premium rate; level initial capital; diffusion model of risk